(untitled) (Historia, 2021)
Thompson's contribution to the historiography of KwaZulu-Natal is welcome. The book is well-researched. The fact that it is predominately based on the archival research, is also commendable. It is "only half a biography" of Bhambatha. It looks at him from his early childhood as "a headstrong boy, fond of fighting". He was very good at shooting and a fast runner. He took over a Zondi chiefdom that had a lot of problems...